Characteristics of colloid silver solution based on changes in concentration and electric field using electrooptic equipment - Heri Sugito; Ketut Sofjan Firdausi; Ali Khumaeni; Syifa Azahra (Diponegoro University Semarang Indonesia, 2021)
Research on the characteristics of colloidal silver solutions based on changes in concentration and electric field using electrooptic devices has been carried out. The purposes of this study was to determine the characteristic of colloidal silver solution based on variations in concentration and electrooptic effects. Electrooptics work based on changes in the polarization angle of the sample. The sample used is a colloidal silver solution with various concentrations. The colloidal silver solution was obtained by laser ablation method and then dissolved in aquabidest. The light source used is a laser pointer with = 532 nm. The electric field applied to the sample is 0-9 kV. The results showed that colloidal silver solution at an angle of 0º showed active plasmon resonance at the peak of polarization with concentrations of 1.9 ppm, 2.28 ppm, and 3.8 ppm. An angle of 90º also shows active plasmon resonance at the peak of polarization with a concentration of 3.8 ppm. From the results, it can be concluded that the characteristics of colloidal silver solution on change in the polarization angle due to an electric field show non-linier properties with increasing concentration.